Pengaruh Aplikasi Google Classroom Terhadap Kepuasan Mahasiswa Menerima Mata Kuliah Pengembangan Diri - Anda Yanny (Cattleya Darmaya Fortuna, 2021)
The corona virus that emerged in early 2020 globally has made massive changes to occur in the world. Starting from the economy, politics to education were affected. The change that has been felt in the world of education is the global implementation of independent study at home. Lecturers are required to deliver learning material through on line, face to face is no longer allowed. Various applications can be used as a means of delivering material. Google classroom is an option that is generally used by educators to deliver material.In this study using SSS 20.00 with the number of questionnaires as many as 30 semester IV Diploma III students of Budi Darma University which aims to see whether there is a relationship between the appearance of Google Classroom and student satisfaction in receiving subject matter Personality Development, Ease of use of Google Classroom on student satisfaction with receiving subject matter. self-development courses and whether the appearance and ease of use of Google Classroom simultaneously affect student satisfaction in receiving self-development course material.